(untitled) (Indian Journal of Animal Production and Management, 2014)
The study was conducted at NRC on Pig (ICAR), Guwahati, Assam to standardize the best age to separate male and female piglets of recently registered Ghungroo pigs for optimizing production performance. Forty Six Ghungroo Piglets of 0.90±0.01 Kg birth weight were selected for the study. Three different treatments of differential age of separation of male and female were done, viz., under control, twelve males and females were separated at an age of 2 months; under T1, Forteen males and females were separated at an age of 3 months; and under T2, twenty males and females were separated at an age of 4 months. Significantly (p<0.05) superior body weight in both males and females was obtained in Control (73.6±5.6) as compared to T1 (70.2±6.5) and T2 (70.7±5.5). Similarly, average daily gain in control was significantly superior. Thus it can be suggested that separation of males and females at an earlier age, viz., just after weaning can fetch superior growth rate and thus can improve the profitability of farmers.